Asset Recovery Handbook : A Guide for Practitioners, Second Edition - Brun, Jean-Pierre (Washington, DC: World Bank, 2020)
The Asset Recovery Handbook: A Guide for Practitioners has been updated in 2020 by the Stolen Asset Recovery (StAR) initiative, a joint initiative of the United Nations Office of Drugs and Crime and the World Bank focused on encouraging and facilitating a more systematic and timely return of stolen assets. Designed as a how-to manual, the handbook guides practitioners as they grapple with the strategic, organizational, investigative, and legal challenges of recovering assets that have been stolen by corrupt leaders and hidden abroad. It provides common approaches to recovering stolen assets located in foreign jurisdictions, identifies the challenges that practitioners are likely to encounter, and introduces good practices. By consolidating into a single framework, information that is dispersed across various professional backgrounds, the handbook has enhanced the effectiveness of practitioners working in a team environment. After 10 years of serving as a recognized reference for practitioners and trainers since it was first published in 2011, the StAR initiative decided to develop this updated version by incorporating developments based on the experience collected during this decade, including new legislation and case examples. This 2020 second edition emphasizes the need to utilize innovative strategies and technical tools, including in the context of international cooperation.